Literature in EFL classes: four teachers' experiences in Brazil - Cardoso, Anna Carolyna Ribeiro; Lago, Neuda Alves do (Revista Investigações, 2021)
Some of the benefits of using literature in EFL classes include improving vocabulary, critical thinking and providing authentic material. Researchers such as Melo Júnior (2015) and Lago (2016; 2017) investigate literature in EFL contexts, noticing how literature can also motivate students. This paper aims to analyze English teachers' experience in Goiás, Brazil, and their relationship with literature in their EFL classes. Its purpose is to investigate whether these teachers use literary works during their lessons. Four teachers were interviewed for this case study. The results show these teachers attribute importance to literature in EFL contexts.